PKM Strategi Kemitraan untuk Pembangunan Kampung Berbasis Collaborative Governance di Kampung Wisata Lambo Sari Malaysia - Febrian, Ranggi Ade; Nazir, Yendri; Azinuddin, Muaz; Setiawan, Panji Rachmat; Fijar, Habibul (LPPM Universitas Pendidikan Mandalika (UNDIKMA), 2025)
This community service activity aims to develop the tourism potential of Lambo Sari Village sustainably through a collaborative governance approach so that it has an impact on improving the quality of life of the community. The method of implementing this service was carried out in the form of discussions and assistance in creating innovation strategies and facilitation from Sultan Zainal Abidin University as a local campus that produces Lambo Sari Village as a fostered village. The targets of this activity were local communities, tourism groups, and business actors. The evaluation instruments used were surveys, field observations, focus group discussions, and documentation. The data analysis technique was in the form of qualitative descriptive analysis. The results of this community service activity were the creation of a network of cooperation between the Islamic University of Riau and the Lambo Sari community group, and assistance to community groups from Sultan Zainal Abidin University in collaboration with the Islamic University of Riau. In addition, this activity provides strategies to community groups in innovative tourism marketing through social media that can be accessed by people across countries.